HUBUNGAN ANTARA PERUBAHAN INKLINASI GIGI ANTERIOR RAHANG ATAS DAN BAWAH DENGAN PERUBAHAN TINGGI WAJAH ANTERIOR BAWAH PADA MALOKLUSI ANGLE KLAS IPROTRUSIFBIMAKSILER ( KajianSefalogram Lateral pada Perawatan Ortodontik dengan TeknikBegg) - , Heri Susilo Winarti; , drg. JCP Heryumani Sulandjari,MS.,SpOrt(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Anterior teeth retraction using Begg technique brings decrease in upper and lower anterior teeth inclination which is marked by the reduction of FIS and IMPA. Z elastic is used in anterior teeth retraction in bimaxillary protrusion case. The horizontal vector of intramaxiller and intermaxiller elastic cause upper and lower anterior teeth retraction, while the vertical vector of intermaxiller elastic cause extrusion of molar teeth, clockwise rotation of the mandible, and an increase of anterior lower face height. The purpose of this study is to understand the relationship between upper and lower anterior teeth inclination change with the change of anterior lower face height in bimaxillary protrusion Angle class I malocclusion treated with Begg technique. Twenty pairs lateral cephalograms which were obtained from 20 patient, each pair consisted of lateral cephalograms before and after orthodontic treatment, were used in this study with inclusion criteria as follows: bimaxillary protrusion Angle class I malocclusion, age 20-35 years old, have finished the orthodontic treatment using Begg technique with four first premolars extraction. FIS, IMPA, and anterior lower face height were measured on each cephalogram which match the inclusion criteria. A Pearsonâs product moment correlation analysis and regression analysis were used to analyze the data obtained from cephalogram measurement. Result showed a significant negative correlation (p<0.05) between upper and lower anterior teeth inclination change with anterior lower facial height. Upper anterior teeth inclination change gave 23.6% of contribution towards the change of anterior lower facial height, while lower anterior teeth inclination change gave 26.3% of contribution. Conclusion: the decrease of lower and upper anterior teeth inclination was accompanied by the increase of anterior lower facial height on protrusive bimaxillary Angle class I malocclusion after treated with Begg technique.